DAMPAK DIGITALISASI USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP PERTUMBUHAN EKONOMI LOKAL DI KABUPATEN SUMBAWA - Ramadhan, Surya Anugerah; Kamal, Afina Aurellya; Haryadi, Wahyu (Pusat Riset dan Publikasi, 2025)
This study aims to determine the impact of digitalization marketing for micro, small, and medium enterprises (MSMEs) on local economic growth in Sumbawa District. The type of this study was comparative study. The type of data used was quantitative data obtained directly from research sources, namely MSME actors in Sumbawa District. The number of MSME actors who were the sources for this study was 60 people who were divided into two groups, namely MSME actors who used digital marketing totaling 30 people and MSME actors who did not use digital marketing totaling 30 people. The data used in this study were collected using structured interview techniques. Data analysis in this study used the two-average difference test technique. The results of this study showed that there are a positive and significant difference in the income of MSME actors who have used digital marketing and MSME actors who have not used digital marketing. The income of MSME actors who have used digital marketing is higher than the income of MSME actors who have not used digital marketing. By using digital marketing, businesses can reach a wider consumer market, thus having a real impact on increasing sales and income earned by MSMEs.